Pre-Clinical Study of General Toxicity of the Medication “Fitin-S” - Kamola Mirzaakhmedova1, Shakhida Ziyayeva2, Abdushukur Yunusov3, Gulchekhra Karimova4, Rustam Karimo (Institute of Medico-legal Publications Pvt Ltd, 2020)
A pre-clinical study of the general toxicity of the medication “Fitin-S” has shown that it is referred toclass IV of low toxic compounds. The medication “Fitin-S” does not have aaccumulative and local irritantaction. At multiple intramuscular administration to rats and rabbits it does not influence the behavior and thedynamics of animals growth, does not cause a toxic effect on the composition of peripheral blood, kidneys’and liver’s function as well as on the pathomorphology of animals organs and tissues. There is a slowdownin the process of blood coagulation in rabbits at doses of 16 and 32 mg/kg during the whole study period.In 1 month of a recovery period all the indicators have been changing within physiological norm. All theaforementioned data allows us to make a conclusion that the medication does not cause a toxic effect on theorganism of animals.